Research on the specific movement of the head in tennis strokes - Fernández López, M. (Coaching and Sport Science Review, 2020)
Technique is one of the aspects that has the most relevant influence on tennis player performance. Searching for more efficient and effective technique, by means of the application of biomechanical laws, is a constant among coaches and researchers. This article deals with a very concrete subject in tennis technique: the position of the head during the impact phase of tennis strokes. Biomechanical aspects of the strokes will also be considered, as well as other relevant aspects such as fixing the gaze during the stroke and the stretching shortening cycle.